2023
DOI: 10.3389/fpsyg.2023.1030043
|View full text |Cite|
|
Sign up to set email alerts
|

The association between workplace ostracism and knowledge-sharing behaviors among Chinese university teachers: The chain mediating model of job burnout and job satisfaction

Abstract: Workplace ostracism is an essential predictor of knowledge-sharing behaviors, but few studies have explored the influence of this mechanism in higher education. According to the conservation of resources theory, this study elucidated the roles of job burnout and job satisfaction as sequential mediators of the link between workplace ostracism and knowledge-sharing behaviors in a sample of 388 university teachers. The results of the study were analyzed via structural equation modeling (SEM). Higher knowledge-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 83 publications
(108 reference statements)
1
6
0
Order By: Relevance
“…35 Workers with a greater degree of education may have higher job expectations and may invest more in their employment, which can contribute to increased stress and fatigue. 36 Other study indicates that workers with a higher education degree may have better abilities and resources to deal with workplace stress, lowering the likelihood of work fatigue. 36,37 According to Obeid et al, education level was not connected to emotional and physical work fatigue with a p-value greater than 0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Workers with a greater degree of education may have higher job expectations and may invest more in their employment, which can contribute to increased stress and fatigue. 36 Other study indicates that workers with a higher education degree may have better abilities and resources to deal with workplace stress, lowering the likelihood of work fatigue. 36,37 According to Obeid et al, education level was not connected to emotional and physical work fatigue with a p-value greater than 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…36 Other study indicates that workers with a higher education degree may have better abilities and resources to deal with workplace stress, lowering the likelihood of work fatigue. 36,37 According to Obeid et al, education level was not connected to emotional and physical work fatigue with a p-value greater than 0.05. 38 Sun et al's study yielded different results, which found a link between education level and work fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…They may be excluded from team activities, social gatherings or relationship-building activities at work (Hua et al, 2023), resulting in reduced interaction with social networks (Zhao et al, 2013) and making it difficult for them to receive help from others to cope with workplace ostracism events. Third, workplace ostracism reduces the job satisfaction and motivation of victims (Anjum et al, 2022;Wang et al, 2023), leading to obstacles in the process of achieving goals and impeding self-worth. This strong sense of goal obstruction and self-deprecation can trigger anger among victims (Mawritz et al, 2014;Zhu and Zhang, 2021).…”
Section: The Mediating Role Of Angermentioning
confidence: 99%
“…In contemporary era, understanding the interaction between job attitudes and knowledge sharing behavior can help organizations develop strategies to foster a culture of knowledge sharing (Nizam & Hameed, 2023). The knowledge sharing phenomenon discusses the exchanges of information, expertise, and experiences among individuals within organization (Wang, Li, Liu & Zaggia, 2023). Knowledge sharing is widely regarded as a fundamental key asset for organizations (Hu &Randel, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It involves the voluntary transmission of knowledge from one person to another, with the aim of enhancing learning, problem-solving, and decision-making processes (Nizam & Hameed, 2023). Thus, by sharing knowledge, individuals can leverage the collective intelligence of the organization, avoid reinventing the wheel, and capitalize on each other's expertise (Wang, Li, Liu & Zaggia, 2023). Similarly, sharing ideas and best practices can stimulate innovation by sparking creativity, identifying new prospects, and solving complex problems collaboratively (Hu & Randel, 2014).…”
Section: Introductionmentioning
confidence: 99%